A pilot study on oral microbiome in electronic cigarettes consumers versus traditional cigarettes smokers - Liu, Jilong; Yue, Qiulin; Zhang, Song; Xu, Jing; Jiang, Xingtao; Su, Qun; Sun, Lei; Li, Baojun; Li, Kunlun; Su, Le; Zhao, Lin (Folia microbiologica, 2025)
Oral microorganisms are closely related to oral health, the occurrence of some oral diseases is associated with changes in the oral microbiota, and many studies have demonstrated that traditional smoking can affect the oral microbial community. However, due to the short time since the emergence of e-cigarettes, fewer studies are comparing oral microorganisms for users of e-cigarettes versus cigarettes. We collected saliva from 40 non-smokers (NS), 46 traditional cigarette smokers (TS), and 27 e-cigarette consumers (EC), aged between 18 and 35 years. We performed 16S rRNA gene sequencing on the saliva samples collected to study the effects of e-cigarettes versus traditional cigarettes on the oral microbiome. The results showed that compared with the NS group, the alpha diversity of oral flora in saliva was altered in the TS group, with no significant change in the e-cigarette group. Compared with the NS and EC groups, the relative abundance of Actinomyces and Prevotella was increased in the TS group. However, compared with the NS and TS groups, the relative abundance of Veillonella was increased, and the relative abundance of Porphyromonas and Peptostreptococcus was decreased in the EC group. These results showed that both e-cigarettes and traditional cigarettes could alter the structure and composition of oral microbiota. The use of traditional cigarettes promotes the growth of some anaerobic bacteria, which may contribute to dental decay and bad breath over time. E-cigarettes have a different effect on the structure and composition of the oral microbial community compared to conventional cigarettes. In order to better understand the effects of e-cigarettes and traditional cigarettes on users' mouths, future studies will investigate the relationship between diseases such as dental caries and periodontitis and changes in oral microbial species levels.
Keywords: sliny; Microbiota; Saliva; mladý dospělý; Traditional cigarettes; Bacteria; kuřáci; kouření; Pilot Projects; Adult; Young Adult; Adolescent; RNA ribozomální 16S; pilotní projekty; mladiství; mikrobiota; Electronic cigarettes; ženské pohlaví; lidé; tabákové výrobky; ústa; RNA, Ribosomal, 16S; Tobacco Products; 16S rRNA; mužské pohlaví; systémy dodávající nikotin elektronicky; Smokers; dospělí; Mouth; Humans; Smoking; Female; Oral flora; Electronic Nicotine Delivery Systems; Male